2021
DOI: 10.1002/adfm.202107838
|View full text |Cite
|
Sign up to set email alerts
|

Bifunctional Catalytic Effect of CoSe2 for Lithium–Sulfur Batteries: Single Doping versus Dual Doping

Abstract: Designing catalysts to accelerate the conversion of soluble lithium polysulfides (LiPSs) is regarded as a promising strategy to inhibit the shuttle effect, improving cathode performance of lithium–sulfur batteries (LSBs). Herein, a bifunctional Ni/Zn dual‐doped CoSe2 is designed to enhance the catalytic effect of CoSe2. Specifically, Ni functions better in catalyzing the conversion of LiPSs into Li2S with shorter CoS bond and longer SS bonds than Zn, while Zn demonstrates a better catalytic effect for Li2S d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 73 publications
(85 reference statements)
1
40
0
Order By: Relevance
“…The Li-S cell with FHCP binder delivers higher specific capacity of 254.9 mAh g -1 than that of Li-S cell with PVDF binder (204.6 mAh g -1 ), demonstrating the effective deposition of Li 2 S caused by FHCP binder. These results clearly confirm that the FHCP binder significantly reduces the overpotential for the initial nucleation of Li 2 S and promotes the precipitation of Li 2 S. [34][35][36] In situ XRD based on Li-S cell with PVDF and FHCP-10 binders was also performed to reveal the evolution mechanism of sulfur species and the redox kinetics during the reaction. As displayed in Figure 5c,d, the diffraction peaks located at 23.14°, 25.92°, 26.82°, and 27.8° are attributed to crystalline α-S 8 (JCPDS 008-0247) at the beginning of discharge.…”
Section: (7 Of 11)supporting
confidence: 52%
“…The Li-S cell with FHCP binder delivers higher specific capacity of 254.9 mAh g -1 than that of Li-S cell with PVDF binder (204.6 mAh g -1 ), demonstrating the effective deposition of Li 2 S caused by FHCP binder. These results clearly confirm that the FHCP binder significantly reduces the overpotential for the initial nucleation of Li 2 S and promotes the precipitation of Li 2 S. [34][35][36] In situ XRD based on Li-S cell with PVDF and FHCP-10 binders was also performed to reveal the evolution mechanism of sulfur species and the redox kinetics during the reaction. As displayed in Figure 5c,d, the diffraction peaks located at 23.14°, 25.92°, 26.82°, and 27.8° are attributed to crystalline α-S 8 (JCPDS 008-0247) at the beginning of discharge.…”
Section: (7 Of 11)supporting
confidence: 52%
“…where ΔV(s) expresses the operating potential window (OPW). 51 while the peaks at ∼778.42 and ∼793.52.4 eV manifest the presence of Co 3+ in the as-prepared electrode material. 48,51 Also, the peaks at ∼784.71 and ∼802.46 eV were the satellite peaks of the Co element.…”
Section: Materials Characterizationmentioning
confidence: 92%
“…Notably, the bidirectional catalyst was also extended to a single component host. 180,181 With spectroscopic investigations and theoretical calculations, it was revealed that an in-built Janus crystal facet self-mediation was onsite constructed by the exposed B and Zr atoms for selective S/Li 2 S conversion in ZrB 2 . 180 Briefly, the smooth "adsorption-conversion" process could be conducted by coupling with enhanced interfacial charge transfer rate 185 when heterostructure is involved.…”
Section: Heterostructurementioning
confidence: 99%